Research on Configurable Workflow Technology in PDM System - Cao Kang; Liu Li; Cheng Zheng (ITM Web of Conferences, 2016)
This paper analyzed the deficiency of the static process management in the traditional PDM workflow system, and proposed a new configurable workflow system model for the dynamic and multiple characteristics of the equipment product design business process. On the basis of PDM workflow engine, the model introduced the configurable workflow form and logic processing program, the total workflow template definition and customized workflow participant selection module, and put forward the key technology solutions. This model could solve the problem of the lack of flexibility in workflow design and maintenance. It had been successfully applied to the design management process for multiple equipment products, and improved the dynamic process management capability of PDM system.